Evaluation of the Technology Agnostic Service Creation Approach - Lau, Sian Lun; Klein, Niklas; Pirali, Andreas; Droegehorn, Olaf; David, Klaus (Electronic Communications of the EASST, 2010)
The current computing and communication services provide convenience and functionality. The creation of these services is however not an easy task. Service development is still mainly technical oriented, where service creation tools are meant for serving and assisting the professional developers. In other words, service creation is not seen as a task for end-users. In our research, we wish to enable service creation for the end-users. This is achieved by introducing the technology agnostic approach into the process. In this paper, we present the conceptual architecture as the proposed solution. Prototype tools were designed and implemented as proof of concept. An evaluation event was held to obtain user feedback on the approach and the prototype tools. This paper presents and discusses the outcome of the evaluation.